Tail function during arboreal quadrupedalism in squirrel monkeys (Saimiri boliviensis) and tamarins (Saguinus oedipus). Issue 8 (14th July 2015) - Young, Jesse W.; Russo, Gabrielle A.; Fellmann, Connie D.; Thatikunta, Meena A.; Chadwell, Brad A.
ABSTRACT The need to maintain stability on narrow branches is often presented as a major selective force shaping primate morphology, with adaptations to facilitate grasping receiving particular attention. The functional importance of a long and mobile tail for maintaining arboreal stability has been comparatively understudied. Tails can facilitate arboreal balance by acting as either static counterbalances or dynamic inertial appendages able to modulate whole‐body angular momentum. We investigate associations between tail use and inferred grasping ability in two closely related cebid platyrrhines—cotton‐top tamarins (Saguinus oedipus) and black‐capped squirrel monkeys (Saimiri boliviensis). Using high‐speed videography of captive monkeys moving on 3.2 cm diameter poles, we specifically test the hypothesis that squirrel monkeys (characterized by grasping extremities with long digits) will be less dependent on the tail for balance than tamarins (characterized by claw‐like nails, short digits, and a reduced hallux). Tamarins have relatively longer tails than squirrel monkeys, move their tails through greater angular amplitudes, at higher angular velocities, and with greater angular accelerations, suggesting dynamic use of tail to regulate whole‐body angular momentum. By contrast, squirrel monkeys generally hold their tails in a comparatively stationary posture and at more depressed angles, suggesting a static counterbalancing mechanism. This study, the first empirical test of functional tradeoffs between grasping ability and tail use in arboreal primates, suggests a critical role for the tail in maintaining stability during arboreal quadrupedalism. Our findings have the potential to inform our functional understanding of tail loss during primate evolution. J. Exp. Zool. 323A: 556–566, 2015. © 2015 Wiley Periodicals, Inc.